Electronic, structural and ferroelectric properties of the ba2zrtio6 double perovskite (2014)
We report the synthesis, the structural characterization, the ferroelectric behavior and the electronic properties of complex perovskite Ba2ZrTiO6. Samples of Ba2ZrTiO6 were synthesized through the standard solid state reaction method. The crystalline structure was studied by means of X-ray diffraction experiments and Rietveld-like analysis. Results reveal that the material crystallizes in a rhomboidal structure, space group R-3 (#148), with cell parameter a=5.8038(7) Å. The ferroelectric response of material was established from curves of polarization as a function of applied electric field. Our results reveal that the double perovskite Ba2ZrTiO6 has a ferroelectric hysteretic behavior at room temperature. The studies of the electronic structure show that Ba2ZrTiO6 behaves as a nonmetallic material with gap energy 2.32 eV. The structural parameters obtained from energy minimization, through the Murnaghan equation state are 99.5% in agreement with the experimental data.